Knowledge, attitude and practice on refractive error among students attending secondary school Mechinagar municipality Japa, Province No. 1, Nepal. - Maharajan,Bijay (2018)
ABSTRACT: This study was conducted in a small-town area of Jhapa, Mechinagra Municipality ward no. 6, which is well known as Kakarbhitta. The major objective of the study was to determine knowledge, attitude and practices on refractive error among school students. For this purpose, descriptive cross sectional study was designed with non-probability sampling method, including student of class 9 and 10 of secondary schools of the area. All total, seven school, 574 students were participated in self-administered questionnaire survey. The major finding of the study are 43.4 percent student had idea about the refractive error, 18.6 percent student were found to have some short of refractive disorder, and myopia is most common. Similarly, wear glass as the common visual impairment correction method and most of these students were bullied and teased of their appearance among the student with refractive error, 84.1 percent got challenge on regular school study.